Analysis of Rejection of The Implementation of The Job Creation Law - Milwan, Milwan; Saputro, Roman Hadi (Jayapangus Press, 2025)
This study examines the widespread rejection of the Job Creation Law in Indonesia by applying policy implementation theory to understand the root causes of public resistance and evaluate government efforts to address these issues. Passed in 2020 using the Omnibus Law approach, the law aims to streamline regulations to boost investment and economic growth. However, the study reveals significant objections from various societal groups, especially workers, due to perceived threats to labor rights, environmental protections, and public participation during its formulation. Using a qualitative literature review method, the research identifies key factors driving resistance, including inadequate transparency, limited stakeholder involvement, and distrust toward the legislative process. The findings show that the law is seen as prioritizing business interests at the expense of workers' welfare and environmental sustainability, exacerbating public dissatisfaction and leading to mass protests across Indonesia. The study underscores the need for effective public communication, inclusive policymaking, and a stronger focus on social welfare to build trust and improve acceptance. Recommendations include increased outreach, revision of contentious provisions, and strengthened collaboration between the government and stakeholders. These steps are critical for achieving a balance between regulatory reform and public trust while addressing Indonesia's socio-economic challenges.